(untitled) (Research, Society and Development, 2022)
The native fruits of the Cerrado are mostly rich in nutrients and have great economic importance for the states where they are located. However, the population that resides in these locations does not always recognize them. Thus, the present work aimed to evaluate the population’s knowledge about the native fruits of the Cerrado biome. To this end, an online form was prepared, in which people reported the frequency of consumption of fruit species and could also identify them. Most of the participants recognized the fruits that were presented, but the young population had the most difficulty. The pequi and the cajuzinho-do-cerrado obtained the highest hit rates and were also indicated as the most consumed fruits, while the guapeva was the least known fruit. Regarding the products processed with fruits from the cerrado commonly found by the participants, the popsicle was the most commonly mentioned product, followed by the jam, the canned fruit, and the juice. Some new products were suggested, being the baru cereal bar the most cited, as well as the pequi snack, the gueroba chips, the buriti cake and the cagaita juice, showing the great variety of products to be researched, processed and marketed.